Cloud Manufacturing as a new type of Product-Service System. Issue 10 (3rd October 2018) - Charro, Alberto; Schaefer, Dirk
ABSTRACT: Industry 4.0 (I4.0) technology developments in Cloud Manufacturing (CMfg) are challenging traditional business models, and adapting these is key to a sustainable competitive advantage. In parallel, pay-per-use strategies are being discussed as an enabler to future sustainable societies. The general benefits of CMfg services are clear, but to date the actual business implications from a service provider perspective have not been discussed. This article explores new business model opportunities based on the idea of providing CMfg as a completely new type of Product-Service Systems. Technology developments and business recommendations are defined, considering the proposed business model targets the manufacturing industry as a whole. Manufacturers make use of their spare capacity by purchasing time on networked equipment on a pay-per-use basis. This allows costs to be brought down, whilst creating new revenue streams. It also increases machine hosts' competitiveness by reducing investment costs and enabling instant manufacturing scalability. CMfg is then classified into three levels of machine autonomy, arguing that as technology develops intermediaries may slowly integrate vertically and eventually replace manufacturers by completely autonomous equipment. The proposed business model presents both a first step and a baseline point of reference towards bridging the gap between advanced manufacturing technology and new business development in the context of I4.0 (Smart Manufacturing).